EFFECT OF THE ROOTS DENSITIES ON THE SHEAR STRENGTH OF ROOT-REINFORCED SOIL - Agus Setyo Muntohar (Teknik Sipil ITS, 2012)
Vegetation on slope was introduced as an alternative technique to prevent the slope failures. Many factors may affect the increases in the shear strength of the root-reinforced soil. This research was undertaken to investigate the effects of the shear strength of soil with the variations of root densities. In this research, a series of laboratory tests was conducted on undisturbed and disturbed samples of soil reinforced with Imperata Cylindrica. The root area ratio (RAR) was estimated from 0.07% to 1.18%. The main laboratory test conducted was direct shear test. The specimen size was in square size of 50 mm by 50 mm and 25 mm of thickness. The relationship between root densities and shear strength of soil was developed. The experimental results revealed that the vegetation roots improved significantly the soil shear strength. The maximum shear strength of the soil increased linearly with the increases in fiber content of the roots. The maximum shear strength was depending on the applied normal stress. A higher normal stress, higher maximum shear strength was obtained. Thus, fibrous root vegetation was playing a significant role in stabilizing the slope.